2015
DOI: 10.1177/0363546515587713
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Remnant Tissue Preservation on Clinical and Arthroscopic Results After Anatomic Double-Bundle Anterior Cruciate Ligament Reconstruction

Abstract: Remnant preservation in anatomic double-bundle ACL reconstruction did not significantly improve subjective and functional results in the short-term evaluation, but it significantly improved postoperative knee stability. The degree of initial graft coverage significantly affected postoperative knee stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
133
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(137 citation statements)
references
References 48 publications
1
133
1
1
Order By: Relevance
“…Through our literature search, 552 potentially relevant studies were identified. After removing duplicate articles (19), 117 were identified by screening titles and abstracts. Finally, five RCTs [5,[10][11][12][13] and six observational studies [14][15][16][17][18][19] were included in this meta-analysis with subgroup analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through our literature search, 552 potentially relevant studies were identified. After removing duplicate articles (19), 117 were identified by screening titles and abstracts. Finally, five RCTs [5,[10][11][12][13] and six observational studies [14][15][16][17][18][19] were included in this meta-analysis with subgroup analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Five RCTs [5,[10][11][12][13] and five observational studies [15][16][17][18][19] reported arthrometric evaluation (KT-1000, KT-2000, Rolimeter, magnitude of side-to-side difference). A total of 472 patients in remnant-preserving groups and 485 patients in non-preserving groups were analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings can be applied to recently described remnant preservation ACL reconstruction techniques. 8,16,19 …”
Section: Discussionmentioning
confidence: 99%
“…эспериментальные исследования, проведен-ные e. Kondo с соавторами, показали, что такие остатки культи пкс, циркулярно прилегая к по-верхности дистальной части трансплантата, обе-спечивают клеточную пролиферацию, регене-рацию проприоцептивных элементов и в итоге уменьшают остаточную нестабильность сустава [14]. но репаративный потенциал пкс после ее разрыва невысок.…”
unclassified